Translation Equivalence in the Song "Mine" by Petra Sihombing with the Indonesian Version - Aryoga Andyrestu (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
This study aims to find out the equivalence of the meaning of the translation of the songs “Mine” and “Milikku” by Petra Sihombing from English to Indonesian, both of which were written by the songwriters themselves. The approach used is a qualitative descriptive approach. The problem faced is the difference in the number of syllables or syllables needed to convey the message in the sentence as a whole with the availability or limitation of syllables in the melody of the song. The method used refers to the translation method according to Mona Baker, which emphasizes the level of equivalence of the meaning of the target language (TL). Two songs that have been translated by the songwriters themselves are used with two different song versions. The results of the study show that the song cannot be translated perfectly into the target language, but the songwriter can translate it as close as possible to the equivalent meaning into the target language by looking at the equivalence of words and meanings, the structure of the song, and the impact of the song on listeners in the target language. so that the message in the song can be conveyed properly.